The Use of English Teaching Methods in a Secondary School in Karawang - Fina Aufar (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2018)
This study focused on the related analysis of English language teaching methods implemented by teachers in MAN 1 Karawang. This study used survey research method, utilising mailed-questionnaire technique. The primary participants of this study were 4 questionnaire responses from English Teachers in MAN 1 Karawang. The result of the study indicated that mostly teachers in MAN 1 Karawang implement Communicative Language Teaching Method, in contrast none of them implement the Project-Based Methods in English Language Teaching and Learning Process. It can be derived from the findings that they have got the well-comprehension about designing the meaningful activities and fulfill the requirement of teaching English in the current era.